In situ assessment of neuroinflammatory cytokines in different stages of ovine natural prion disease - Guijarro, Isabel M.; Garcés, Moisés; Badiola, Juan J.; Monzón, Marta (Frontiers in Veterinary Science, 2024)
IntroductionAccording to the neuroinflammatory hypothesis, a cytokine-mediated host innate immune response may be involved in the mechanisms that contribute to the process of neurodegeneration. Specifically, regarding prion diseases, some experimental murine models have evidenced an altered profile of inflammatory intermediaries. However, the local inflammatory response has rarely been assessed, and never in tissues from different natural models throughout the progression of neurodegeneration.MethodsThe aim of this study was to use immunohistochemistry (IHC) to in situ assess the temporal protein expression of several cytokines in the cerebellum of sheep suffering from various clinical stages of scrapie.Results and discussionClear changes in the expression of most of the assessed markers were observed in the affected sheep compared to the healthy control sheep, and from different stages. In summary, this preliminary IHC study focusing in the Purkinje cell layer changes demonstrate that all cytokines or respective receptors studied (IL-1, IL-1R, IL-2R, IL-6, IL-10R, and TNFαR) except for IFNγR are disease-associated signaling proteins showing an increase or decrease in relation to the progression of clinical disease. In the future, this study will be extended to other inflammatory mediators and brain regions, focusing in particular on the release of these inflammatory mediators by astroglial and microglial populations.